2008
DOI: 10.1016/j.biomaterials.2008.08.019
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fatigue crack growth in human enamel and hydroxyapatite

Abstract: Cracks and craze lines are often observed in the enamel of human teeth, but they rarely cause tooth fracture. The present study evaluates fatigue crack growth in human enamel, and compares that to the fatigue response of sintered hydroxyapatite (HAp) with similar crystallinity, chemistry and density. Miniature inset compact tension (CT) specimens were prepared that embodied a small piece of enamel (N=8) or HAp (N=6). The specimens were subjected to mode I cyclic loads and the steady state crack growth response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…Previous studies of enamel fracture have observed cracks more commonly along rod boundaries than running through rods (Ramussen et al 1976). Bridges of 10-20µm wide in enamel have been observed in several previous experimental studies (Bajaj and Arola, 2009a, 2009b; Bechtle et al, 2010a;Bajaj et al, 2008); they span across multiple rods. In this study, bridges of 3µm wide are observed along interrod regions of the width of one enamel rod (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous studies of enamel fracture have observed cracks more commonly along rod boundaries than running through rods (Ramussen et al 1976). Bridges of 10-20µm wide in enamel have been observed in several previous experimental studies (Bajaj and Arola, 2009a, 2009b; Bechtle et al, 2010a;Bajaj et al, 2008); they span across multiple rods. In this study, bridges of 3µm wide are observed along interrod regions of the width of one enamel rod (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…In a number of other studies Arola, 2009a, 2009b;Bechtle et al, 2010;Bajaj et al, 2008] enamel's toughening mechanisms are already reported but not with a special focus on the different lengths scales. As enamel is hierarchically structured the objective is to identify the specific toughening mechanisms on the first and second hierarchical level as defined above using AFM and SEM.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, many researchers reported the fracture toughness ( IC(e) ) of enamel nanocomposite [24,25,27,30,31,34,35,[37][38][39]. The IC(e) at DEJ zone was reported to be 0.8 to 0.9 MPa⋅m 0.5 [37].…”
Section: Introductionmentioning
confidence: 99%
“…The HAp crystal has an anisotropic elastic modulus, as determined by a technique based on elastic wave propagation (Gardner et al, 1992) and by nano-indentation measurements (Zamiri and De, 2011). The mechanical properties of macroscopic enamel tissue are strongly dependent on the alignment and orientation of the HAp crystals, as found from elastic modulus (Habelitz et al, 2001) and fatigue toughness (Bajaj et al, 2008) measurements. The strain behavior of HAp in mineralized tissue has been extensively studied using synchrotron X-ray sources that generate high-brightness X-rays for bone tissue Stock, 2005, 2007;Gupta et al, 2006aGupta et al, , 2006b) and for tooth dentin and tooth enamel (Almer and Stock, 2010).…”
Section: Introductionmentioning
confidence: 99%